Review of past research and proposed action plan for landfill gas-to-energy applications in India. Issue 1 (January 2013) - Siddiqui, Faisal Zia; Zaidi, Sadaf; Pandey, Suneel; Khan, Mohd Emran
Open dumps employed for disposal of municipal solid waste (MSW) are generally referred to as landfills and have been traditionally used as the ultimate disposal method in India. The deposition of MSW in open dumps eventually leads to uncontrolled emission of landfill gas (LFG). This article reviews the MSW disposal practices and LFG emissions from landfills in India during the period 1994 to 2011. The worldwide trend of feasibility of LFG to energy recovery projects and recent studies in India indicate a changed perception of landfills as a source of energy. However, facilitating the implementation of LFG to energy involves a number of challenges in terms of technology, developing a standardized framework and availability of financial incentives. The legislative framework for promotion of LFG to energy projects in India has been reviewed and a comprehensive strategy and action plan for gainful LFG recovery is suggested. It is concluded that the market for LFG to energy projects is not mature in India. There are no on-ground case studies to demonstrate the feasibility of LFG to energy applications. Future research therefore should aim at LFG emission modeling studies at regional level and based on the results, pilot studies may be conducted for the potential sites in the country to establish LFG to energy recovery potential from these landfills.